Assessment of Co-Variance for Transmission Flow Series-Parallel Reliability Systems - Razak, K. Abdul; Rajakumar, K. (Journal of physics. Conference series, 2019)
A methodical hypothesis of dependability depends on likelihood hypothesis. It is outstanding that the ordinary unwavering quality examination utilizing the probabilities has been observed to be insufficient to deal with the uncertainty of disappointment in information and displaying. The fluffy set hypothesis gives a helpful instrument to supplement customary dependability speculations. This paper proposes the transmission stream framework outline in arrangement parallel structure to assess the most extreme unwavering quality subject to the frame work cost. The co-productive of variation (CV) is acquainted with evaluate every enrollment work. This approach is to discover least CV with high reliability gauge.